The use of the soluble receptor for advanced glycation-end products (sRAGE) as a potential biomarker of disease risk and adverse outcomes - Erusalimsky, Jorge D. (Redox Biol, 2021)
The soluble receptor for advanced glycation end-products (sRAGE) has been classically considered a sink for pro-inflammatory RAGE ligands and as such has been associated with protection from inflammatory stress and disease. An alternative, though not mutually exclusive view is that high levels of sRAGE in circulation reflect the overstimulation of cell surface RAGE which if persistent, lead to the amplification of pro-inflammatory processes and the exacerbation of pathological states. With these two scenarios in mind this review focuses on the potential role of sRAGE as a prospective biomarker of disease risk and adverse outcomes.